1997
DOI: 10.1038/sj.ejcn.1600466
|View full text |Cite
|
Sign up to set email alerts
|

Dietary triglycerides, up to 40 g/meal, do not affect preformed vitamin A bioavailability in humans

Abstract: Objective: Assessing the effect of the dose of dietary triglycerides on preformed vitamin A (retinyl esters) bioavailability in humans. Design: Four test meals containing 15 000 RE retinyl-palmitate and either 0, 15, 30 or 40 g added triglycerides were ingested by eight healthy volunteers, at different days and in a randomized order. Setting: The study was done in the Hospital Sainte Marguerite, Marseille, France. Subjects: Eight healthy male volunteers were recruited by advertisement. Intervention: Blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 25 publications
(38 reference statements)
1
18
0
1
Order By: Relevance
“…(VLDLA) fractions. Measuring the appearance of retinyl esters only in the chylomicron component of the TRL underestimates total vitamin A absorption (34). In a previous study, after subjects ingested a b-carotene dose, we observed postprandial appearances of retinyl palmitate in both the plasma chylomicron and VLDLA fractions that coincided in time and magnitude (35).…”
Section: Discussionmentioning
confidence: 90%
“…(VLDLA) fractions. Measuring the appearance of retinyl esters only in the chylomicron component of the TRL underestimates total vitamin A absorption (34). In a previous study, after subjects ingested a b-carotene dose, we observed postprandial appearances of retinyl palmitate in both the plasma chylomicron and VLDLA fractions that coincided in time and magnitude (35).…”
Section: Discussionmentioning
confidence: 90%
“…HPLC was able to distinguish between retinyl myristate, palmitate, and stearate concentrations (26,27). Only retinyl myristate was present at significant levels before retinol incubation ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The cells were collected by scraping, resuspended in PBS, and sonicated on ice. All-trans retinol and retinyl esters were assayed from 1g of placental tissue, 5 ϫ 10 6 cells, or 0.5 mL of culture medium, as previously described with some minor modifications (26,27). An equal volume of ethanol containing an internal standard (retinyl laurate for vitamin A) was added to each sample.…”
mentioning
confidence: 99%
“…The presence of dietary fat in the intestine usually increases intestinal absorption of preformed vitamin A and provitamin A carotenoids by enhancing the secretion of pancreatic enzymes and of bile salts that provide components (lysophospholipids, monoglycerides, free fatty acids) to form luminal mixed micelles of lipids and for intracellular assembly of chylomicrons (Roels et al, 1958;Roels et al, 1963;Reddy and Srikantia, 1966;Figueira et al, 1969;Jayarajan et al, 1980;Borel et al, 1997;Jalal et al, 1998;Li and Tso, 2003;Unlu et al, 2005).…”
Section: Intestinal Absorptionmentioning
confidence: 99%